Estudo de dureza e de propriedades superficiais do compósito epóxi/quasicristal - Barros, Thayza Pacheco dos Santos (2015)
Quasicrystals are materials with unique properties such as high hardness, low surface energy, low coefficient of friction, etc. Due to its high hardness and consequent fragility, the use of quasicrystals becomes limited to coatings and composite materials. This paper is a study of hardness and surface properties of the composite formed by the epoxy matrix and the quasicrystalline reinforcement. The quasicrystalline alloy Al59,2Cu25,5Fe12,3B3 were obtained by melting and made into powder by hand. Then it was ground by high energy milling to reduce the particle size. After milling the powder, it was added in the polymer matrix in volumetric ratios of 1, 10, 20 and 30% where the comparison of the properties was made between the composite of QC on the composite and the pure epoxy resin. For the characterization of quasicristalino powder, we used the X-Ray Diffraction (XRD), Sieve Analysis and Scanning Electron Microscopy (SEM), while for the composite we used the Thermogravimetric Analysis techniques, Shore D hardness test Analysis of the Angle of Contact and SEM. By measuring the contact angle was possible the realization of surface energy calculations and work of adhesion between the constituents. Through this study it is concluded that it was possible to obtain a composite QC / Epoxy with greater hardness and still maintain its surface characteristics.